PENTINGNYA ETIKA PROFESI DALAM LINGKUNGAN ASRAMA MELALUI MEDITASI - dealmus_19; Kusnanto; Shanti Thomas (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2024)
This research aims to explore the importance of professional ethics in a dormitory environment through meditation practice. Meditation is seen as a tool to strengthen the application of ethical values ??such as integrity, responsibility, respect, and honesty among hostel residents. The research method used was qualitative with an exploratory approach, involving participant observation and in-depth interviews with dormitory residents who were involved in meditation practices. The results showed that meditation significantly improved self-awareness, emotional management, and the quality of social interactions in the dormitory environment. Practical implications of this research include the integration of meditation as part of character development programs in dormitories as well as improving the quality of life of residents through more effective conflict management and a calmer atmosphere.